Fruit and Seed Development of Citrus aurantifolia (Christm.) Swingle ‘Pan Rampai’ Cultivar - Chuenwarin, Paweena; Raksajan, Kranpitcha; Charoenphon, Penpitcha; Thongleow, Sukawat; Sastawittaya, Samart; Pagamas, Piyanath (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2024)
The ‘Pan Rampai’ cultivar of Mexican lime is highly consumed for its lime aroma and high juice content. However, occasional instances of low juice content could be found, potentially due to premature harvesting. Moreover, the seed development of the ‘Pan Rampai’ lime has never been investigated. Hence, this study was aimed to explore the development process of the ‘Pan Rampai’ lime fruit, focusing on its fruit weight, juice weight, juice content, fruit diameter, fruit length, fruit rind thickness, total soluble solids, titratable acid, TSS/TA ratio, and vitamin C content over the period of 11 to 18 weeks after flowering (WAF). Additionally, we examined the seed development by observing seed width, length, thickness, and germination percentage. Our findings revealed that fruit weight, juice weight, juice content, fruit diameter, and fruit length exhibited a consistent increase throughout the fruit development stages, while the fruit rind thickness decreased. Seed width and thickness remained relatively stable over 11 to 18 WAF, whereas seed length gradually increased. The study of germination percentage indicated that seed germination was mature from the 15th WAF, coinciding with the appearance of the secondary wall of seed coat. There results provide crucial insights into the optimal harvesting periods for juice (from 17 WAF) and seed (from 15 WAF) for the ‘Pan Rampai’ lime cultivar.